2023
DOI: 10.7759/cureus.36299
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Video Quality and Reliability of YouTube Videos Regarding Meniscus Tear Rehabilitation

Abstract: Introduction:YouTube is an open-source platform where creators can record and upload videos for others to see. As the popularity of YouTube increases, it is being increasingly used for healthcare-related information. However, with the relative ease of uploading videos, the content quality of individual videos is not regulated. This study aimed to assess and analyze the content quality of YouTube videos concerning meniscus tear rehabilitation. We hypothesized that most videos would be of low quality.Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…In addition to the PEMAT-A/V, the modified DISCERN tool was used to assess the quality of medical information in the videos. This tool has been widely employed in various studies for the evaluation of medical video quality and has shown correlations with other quality assessment tools such as the Journal of American Medical Association (JAMA) score, and Global Quality Score (GQS) 9 , 12 , 13 . Our findings indicated relatively lower modified DISCERN scores for video clips produced by non-otolaryngologists, or 'others', with particular deficits observed in the reliability and reference sections of the assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the PEMAT-A/V, the modified DISCERN tool was used to assess the quality of medical information in the videos. This tool has been widely employed in various studies for the evaluation of medical video quality and has shown correlations with other quality assessment tools such as the Journal of American Medical Association (JAMA) score, and Global Quality Score (GQS) 9 , 12 , 13 . Our findings indicated relatively lower modified DISCERN scores for video clips produced by non-otolaryngologists, or 'others', with particular deficits observed in the reliability and reference sections of the assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Each point is allocated for concision, reliability, balance, reference, and uncertainty (Table 2 ). This tool was previously utilized in several studies for the same purpose 9 , 12 , 13 . The score comprises five yes/no questions, with 1 point given for each "yes" answer and 0 points for "no".…”
Section: Methodsmentioning
confidence: 99%
“…This scoring tool is composed of 15 items directly from the guidelines published by the American Academy of Orthopedic Surgeons, which is a method shown to be feasible and accepted in previous literature. 8 , 10 , 13 , 14 , 18 , 19 , 20 , 21 , 22 One point is assigned for each of the 15 items that are present in the video, and higher scores (max of 15) indicate greater Dupuytren’s contracture-specific content quality.…”
Section: Methodsmentioning
confidence: 99%
“…In 2022, more than 35000 certi ed doctors uploaded about 4.43 million popular science videos on TikTok [4]. Meanwhile, Toutiao and Bilibili are also popular and essential channels for health information dissemination in China, with user-friendly experiences on computers, tablets, and smart mobile phones [5]. However, since video-sharing platforms always focus more on entertainment rather than education and professional knowledge, current research suggested that medical content on video-sharing platforms is variable and not comprehensive [6], with questionable authenticity and credibility [7].…”
Section: Introductionmentioning
confidence: 99%
“…Since medical information on video-sharing platforms has great potential on guiding patients and educating medical students, low-quality and even misleading content may have secondary effects on harming the physical and mental health of the public and the healthy development of the online healthcare industry [13] [14]. As patients continue to turn to the internet for health information and use this information in decision-making related to their health, it is important that the information presented online should be accurate and thorough [15].…”
Section: Introductionmentioning
confidence: 99%